E-Government implementation challenges in small countries: The project manager's perspective - Glyptis, Loukas; Christofi, Michael; Vrontis, Demetris; Giudice, Manlio Del; Dimitriou, Salomi; Michael, Panayiota (My University, 2020)
E-Government is a global trend with far-reaching benefits if implemented in the optimal way. All nations, irrespective of whether they are considered developed or developing economies, invest in the development of strategies furthering their e-government agenda. While e-government has attracted extensive interest for over a decade, leading to a maturing field, small European Union (EU) members have some particularities that must be taken into account. This research focuses on the critical success factors of e-government adoption, using the Republic of Cyprus as a case study. These findings show that the financial position of a nation and its e-readiness level, as well as the infrastructure facilities and technological innovations for effective knowledge management and communication, political and legal frameworks, are key factors that influence the level of e-government adoption. Furthermore, organizational and institutional aspects, as well as the socio-cultural characteristics, should not be underestimated, as these factors are crucial barriers to e-government adoption. Finally, the specific country's environmental cognition and consciousness is found to be more influential in this case than what literature on other cases suggest.
Keywords: Critical success factors; E-government; E-projects; Knowledge management; Project management